Improving Quality Assurance in Manufacturing Companies Through the Genba Walk Improvement Process - Ferdi Saepulah; Teuku Yuri M. Zagloel (Al-Makki Publisher, 2026)
The automotive manufacturing industry faces increasing challenges in maintaining product quality, operational efficiency, and compliance between Standard Operating Procedures (SOPs) and actual practices in the production process. Inconsistent implementation of operational standards often leads to defects, rework, process instability, and reduced quality performance. This study aims to analyze the effect of Genba Walk Improvement on SOP-Actual Alignment and Quality Performance in automotive manufacturing companies. The research employed a quantitative approach using survey methods involving 150 respondents consisting of analysts, engineers, section heads, and department heads working in multinational motorcycle manufacturing companies. Data were collected through observations, interviews, literature studies, and online questionnaires. The analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) supported by SPSS and SmartPLS 3.0 software. The variables examined included Genba Walk Standardization, Genba Walk Execution, Genba Walk Evaluation, SOP-Actual Alignment, and Quality Performance. The results revealed that all variables had positive and significant relationships. Structured and consistent Genba Walk practices were proven to strengthen SOP compliance, reduce process deviations, minimize defects and rework, and improve production stability and customer satisfaction. The study concludes that Genba Walk functions not only as a field observation activity but also as an effective Lean management and quality control mechanism that supports continuous improvement and sustainable operational excellence in manufacturing industries.